DEVELOPING EXTENDED WORK ORDER MANAGEMENT SYSTEM FOR GARMENT PRODUCTION USING SYSTEM DYNAMIC AND CIRCULAR ECONOMY APPROACH: CASE STUDY POLITEKNIK STTT BANDUNG - Tomi
Politeknik STTT Bandung is a vocational higher education institution under the Ministry of Industry, comprising five programs: four undergraduate (D-IV) programs and one master's program (S2). This research focuses on the Garment Production department, which routinely conducts production activities for laboratory coats and PDL shirts as part of its practical coursework. The Garment Production department operates a make-to-order production system, where production is based on received orders. However, the production processes in the Garment Production department still rely on a traditional production system, in which all activities are carried out manually. This manual approach presents challenges in monitoring, tracking, reporting, and measuring the efficiency of the overall production system. Furthermore, Garment Production department applies a linear economy model in it production process, where fabric waste from production is disposed without being reused. To address these issues, a work order management system was designed using a system dynamics and circular economy approach. The system dynamics approach is used to evaluate the current system performance and predict performance under a circular economy model. The results of the system dynamics simulation, which include several key parameters, serve as inputs for the proposed work order management system. This system not only enables the reuse of fabric waste but also enhances the monitoring and evaluation of the entire production process. The work order management system is developed using the Accelerated SAP (ASAP) methodology and implemented on the opensource enterprise system Odoo. The research involves several stages, including, observation, interviews, literature review, analysis, and system design through the configuration, customization, and testing of Odoo modules. The result of this research is an Odoo-based ERP system with modules tailored to the outcomes of the system dynamics simulation and the requirement of Garment Production Departement.